i have an algebraic expression to evaluate =

8x+9y-(2x+y)

x=4 and y =6

this is how im doing it

step 1 : 8x+9y -8x+ (-6y)

answer book states answer is 72 how is that im suppose to get that number

im severely confused as to what im doing wrong

Printable View

- August 7th 2012, 05:44 PMtonygggggalgebraic expression
i have an algebraic expression to evaluate =

8x+9y-(2x+y)

x=4 and y =6

this is how im doing it

step 1 : 8x+9y -8x+ (-6y)

answer book states answer is 72 how is that im suppose to get that number

im severely confused as to what im doing wrong - August 7th 2012, 06:22 PMMrdavid445Re: algebraic expression
With the equation 8x+9y-(2x+y), we simply plug in 4 for x and 6 for y, thus giving us 8*4+9*6-(2*4+6)=72, our desired answer

- August 7th 2012, 06:23 PMMrdavid445Re: algebraic expression
My question to you is why you turned -2x to -8x and -y to -6y?

- August 8th 2012, 02:11 AMkraj8995Re: algebraic expression
We have not turned the -2x into -8x.We have put 4 in -2x=-2*4=-8

-y=-6.

so we get answer 72.

trigonometry